STRATEGI KOMUNIKASI ELITE LOKAL DAN UMAT HINDU DALAM PRAKTIK TABUH RAH PENGANGON PADA MASA PANDEMI COVID-19 DI DESA ADAT KAPAL KECAMATAN MENGWI KABUPATEN BADUNG - I Ida Bagus Surya Negara; Ida Bagus Gede Candrawan; Made Redana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2021)
One of the traditions in Bali that is still preserved today is the Tabuh Rah Pengangon Tradition in Subak Tegan, Traditional Village of Kapal. This tradition is carried out once a year at harvest. In 2019 the world was shocked by the Covid19 virus. The development of the virus is quite massive and the increase in cases in Indonesia has resulted in the government taking preventive measures by implementing Large-Scale Social Restrictions (PSBB). With circulars from the Bali provincial government and PHDI, the role of local elites is important in conveying information to the public. This study focuses on discussing the essence and communication strategies used by local elites and Hindus as well as the religious system that took place during the Covid-19 Pandemic. This study uses a qualitative method with an empirical approach. Data collection was done by interview and observation techniques. The results show that the essence of communication used is ritual communication which is carried out as a form of habitual behavior. The communication strategy between local elites and Hindus is divided into 3 stages, namely the planning stage by holding sangkep, the preparation stage by distributing notification letters by kesinoman and the implementation stage of the local elite overseeing the event. During the pandemic, the Tabuh Rah Pengangon tradition process continues, it's just that the implementation is now limited to 25 people, the venue is reduced and the health protocol is still implemented